AKTIVITAS EKSTRAK RIMPANG TEMULAWAK (Curcuma xanthorrhiza Roxb.) PADA RADIAL ARM MAZE DAN PASIVE AVOIDANCE TEST TIKUS MODEL DEMENSIA - Didik Yuni Prasetya; Sapto Yuliani (Pharmaciana, 2014)
Curcuma xanthorrhiza Roxb. is a plant containing curcumin. Curcumin has been shown toreduce oxidative damage and memory deficits associated with aging. The aim of the researchwas to know the effect of Curcuma xanthorrhiza Roxb. rhizome ethanol extract to memoryfunction on Wistar rats induced by trimethyltin. The research design was post test onlycontrolled group with 42 rats divided into 6 groups, Each group consist of 7 rats. Group I(healthy controls) were given a solution of 0.5% CMC-Na orally. Group II (negative control)were given a solution of 0.5% CMC-Na orally. Group III, IV, and V were given Curcuma xanthorrhiza Roxb. extract each 120 mg/kgBW, 240 mg/kgBW, and 480 mg/kgBW orally.Group VI (positive control) were given piracetam 500 mg/kgBW intraperitoneally. All groupswere given trimethyltin intraperitoneally except group I. Data indicating memory function wereobtained from radial maze test and passive avoidance test. Radial maze test data were analyzedby ANOVA followed by LSD test, while the passive avoidance test data were analyzed with theKruskal Wallis test followed by Mann-Whitney test. In conclusion, ethanol extract oftemulawak rhizome (Curcuma xanthorrhiza Roxb.) at doses of 120 mg/kgBW, 240 mg/kgBWand 480 mg/kgBW can prevent memory function decline on Wistar rats induced bytrimethyltin.